Analisis Kinerja Alat Berat Pada Proyek Normalisasi dan Perkuatan Tebing Sungai - Jaya, Ansar; Lakawa, Irwan; Hawa, Sitti; Bona, Muh Samtun (Universitas Sulawesi Tenggara, 2022)
The purpose of this study was to analyze the performance of heavy equipment and the duration of time required to complete the Windo River Cliff Normalization and Reinforcement Project, Pamandati Village, Laeya District, South Konawe Regency. The results showed that the excavator's performance in excavation work (mechanical) was 38.68 m3/hour, dump truck 2.99 m3/hour. As for the embankment work imported from outside, the performance of the excavator is 98.53 m3/hour and the dump truck is 3.05 m3/hour. Where the duration of time required to complete the excavation work (mechanical) with an excavator is 12 days and for embankment work imported from outside is 2 days..